2003
DOI: 10.1002/ijc.11033
|View full text |Cite
|
Sign up to set email alerts
|

Human malignant glioma cell lines are sensitive to low radiation doses

Abstract: Malignant gliomas display aggressive local behavior and are not cured by existing therapy. Some cell lines that are considered radioresistant respond to low radiation doses (<1 Gy) with increased cell killing (low-dose hypersensitivity). In our study, 4 of 5 human glioma cell lines exhibited significant X-ray sensitivity at doses below 1 Gy. The surviving fractions (SFs) obtained at 0.7 and/or 0.8 Gy were comparable to those at 1.5 Gy. Low-dose hypersensitivity was evident when irradiation was combined with et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
61
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 47 publications
4
61
0
Order By: Relevance
“…31 However, in another recent report, repeated irradiation with low dose (0.8 Gy 3 times / day for 4 days/week to a total of 2 consecutive weeks) was markedly more effective than irradiation with single conventional dose (2 Gy / day, for 4 days/week to a total of 2 consecutive weeks) in inhibiting the tumor xenograft in mice. 33 The authors implied that the ultra-fractionation as apposed to continuous hyperfractionation accelerated radiotherapy, reduced long-term injuries and prevented tumor repopulation in radioresistant tumors. 33 These reported findings are in concordance with results observed in our study where the LDFRT group showed a significant inhibitory effect and a prolonged tumor regrowth delay when compared with 2 Gy group ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 However, in another recent report, repeated irradiation with low dose (0.8 Gy 3 times / day for 4 days/week to a total of 2 consecutive weeks) was markedly more effective than irradiation with single conventional dose (2 Gy / day, for 4 days/week to a total of 2 consecutive weeks) in inhibiting the tumor xenograft in mice. 33 The authors implied that the ultra-fractionation as apposed to continuous hyperfractionation accelerated radiotherapy, reduced long-term injuries and prevented tumor repopulation in radioresistant tumors. 33 These reported findings are in concordance with results observed in our study where the LDFRT group showed a significant inhibitory effect and a prolonged tumor regrowth delay when compared with 2 Gy group ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…33 The authors implied that the ultra-fractionation as apposed to continuous hyperfractionation accelerated radiotherapy, reduced long-term injuries and prevented tumor repopulation in radioresistant tumors. 33 These reported findings are in concordance with results observed in our study where the LDFRT group showed a significant inhibitory effect and a prolonged tumor regrowth delay when compared with 2 Gy group ( Fig. 2A and B).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] Strikingly, this "radiosensitivity" is more apparent in radioresistant cell lines, such as glioma cells. [8][9][10][11][12][13][14][15][16][17] We demonstrated this phenomenon in a number of various human malignant glioma cell lines using a common clinical device for irradiation. 7,17 Daily irradiation with a single biologically equivalent dose resulted in significantly higher cell death (using a clonogenic assay).…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] We demonstrated this phenomenon in a number of various human malignant glioma cell lines using a common clinical device for irradiation. 7,17 Daily irradiation with a single biologically equivalent dose resulted in significantly higher cell death (using a clonogenic assay). 7,17 Experiments conducted on glioma xenografts revealed that repeated irradiation with low doses (0.8 Gy, three times a day) is more effective than a single dose (2 or 2.4 Gy, once a day) in inhibiting tumor growth.…”
mentioning
confidence: 99%
See 1 more Smart Citation